2017
DOI: 10.18632/oncotarget.15121
|View full text |Cite
|
Sign up to set email alerts
|

Combination antiretroviral therapy (cART) restores HIV-1 infection-mediated impairment of JAK-STAT signaling pathway

Abstract: JAK-STAT signaling pathway has a crucial role in host innate immunity against viral infections, including HIV-1. We therefore examined the impact of HIV-1 infection and combination antiretroviral therapy (cART) on JAK-STAT signaling pathway. Compared to age-matched healthy donors (n = 18), HIV-1-infected subjects (n = 18) prior to cART had significantly lower expression of toll-like receptors (TLR-1/4/6/7/8/9), the IFN regulatory factors (IRF-3/7/9), and the antiviral factors (OAS-1, MxA, A3G, PKR, and Tetheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…In the cytosol of pDCs, HIV nucleic acid is presented to TLR7 located in endosomes, which is transferred from the endoplasmic reticulum (ER) to endosome via polytopic membrane protein UNC93B1 and heat shock protein gp96 ( 27 , 28 ). After the formation of endosomes, TLR7 rapidly catches up with single-strand RNA (ssRNA) ( 29 ). But the specific character of these ssRNA has not been identified.…”
Section: The Induction Of Ifn-i In the Process Of Hiv-1 Infectionmentioning
confidence: 99%
“…In the cytosol of pDCs, HIV nucleic acid is presented to TLR7 located in endosomes, which is transferred from the endoplasmic reticulum (ER) to endosome via polytopic membrane protein UNC93B1 and heat shock protein gp96 ( 27 , 28 ). After the formation of endosomes, TLR7 rapidly catches up with single-strand RNA (ssRNA) ( 29 ). But the specific character of these ssRNA has not been identified.…”
Section: The Induction Of Ifn-i In the Process Of Hiv-1 Infectionmentioning
confidence: 99%
“…Some HIV proteins have been reported to inhibit effective IFNα signalling by degrading certain components of the JAK/STAT signalling pathway like STAT1 and STAT3 [ 50 ]. The impaired JAK/STAT signalling pathway is however restored in the presence of uninterrupted combined Antiretroviral therapy (cART) for more than 6 months [ 51 ]. Per our search, we found one study available on HIV/COVID-19 signalling pathway that investigated STAT3 but did not look at other STAT pathways [ 52 ], and therefore creates a gap that needs to be researched.…”
Section: Discussionmentioning
confidence: 99%
“…Some efforts are in early stages and involve the use of combination antiretroviral therapy (cART). A recent study showed the impact of cART in HIV-1 infection by examining the JAK-STAT signaling pathway which plays a crucial role in host innate immunity against HIV-1 [26]. The JAK-STAT signaling pathway is involved in Toll-like receptor (TLR)-mediated pathogen recognition, IRF activation and the induction of IFN-inducible genes such as MxA and ISG56.…”
Section: Example Of Virusesmentioning
confidence: 99%
“…Therefore, they postulated that deficiencies in the JAK-STAT pathway may play a role in the immunopathogenesis of HIV-1 disease. These new directions are focused on latency-reversing agents to activate immunotherapies, gene therapies, and therapeutic vaccines to eliminate persistent HIV reservoirs or induce effective immune control of HIV infection [26].…”
Section: Example Of Virusesmentioning
confidence: 99%